A brief intervention increases fruit and vegetable intake: a comparison of two intervention sequences - Lhakhang, P. (2015)
Background and Purpose: To evaluate the effectiveness of two subsequent intervention components (motivational and self-regulatory components), placed in different order, to promote fruit and vegetable (FV) intake. Methods: After baseline assessment, university students (N = 205, aged 18-26 years) were allocated to two groups. One group received a motivational intervention (outcome expectancies, risk perception, and task self-efficacy) followed by a self-regulatory intervention (planning and dietary self-efficacy) after 17 days. The second group received the same intervention conditions in the opposite order. Follow-up assessments were done after another 17 days. Results: Both intervention sequences yielded gains in terms of FV intake and self-efficacy. However, this gain was only due to the self-regulatory component whereas the motivational component did not contribute to the changes. Moreover, changes in intention and self-efficacy mediated between intervention sequence and follow-up behavior, suggesting that improving these proximal predictors of FV intake was responsible for the behavioral gains. Conclusions: Findings highlight the superiority of a self-regulatory intervention over a motivational intervention when it comes to dietary changes in this sample of young adults. Moreover, changes in dietary self-efficacy may drive nutritional changes.